2019
DOI: 10.1111/vop.12701
|View full text |Cite
|
Sign up to set email alerts
|

Equine infectious keratitis in Finland: Associated microbial isolates and susceptibility profiles

Abstract: ObjectiveTo retrospectively describe laboratory findings, treatment, and outcome associated with equine infectious keratitis in Finland.Animals and proceduresMedical records of horses diagnosed with infectious keratitis in University of Helsinki Equine Hospital from January 2007 to June 2018 were reviewed.ResultsForty‐seven cases were included. Keratomycosis was diagnosed in 27 eyes and bacterial keratitis in 20 eyes. Aspergillus flavus was the most frequent fungal isolate (9/17, 53%), followed by Cylindrocarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 46 publications
6
33
0
1
Order By: Relevance
“…Bacteria were not always isolated when infection was clinically suspected (mucopurulent discharge, keratomalacia, stromal cellular infiltration, and/or anterior chamber inflammation) while bacteria were isolated in some cases when clinical signs of infection were not present. In accordance with previous published data based on culture‐dependent methods, gram‐positive bacteria were most commonly identified (80.6%) in horses with an infectious ulcerative keratitis in Belgium 3,9,11–14 . Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bacteria were not always isolated when infection was clinically suspected (mucopurulent discharge, keratomalacia, stromal cellular infiltration, and/or anterior chamber inflammation) while bacteria were isolated in some cases when clinical signs of infection were not present. In accordance with previous published data based on culture‐dependent methods, gram‐positive bacteria were most commonly identified (80.6%) in horses with an infectious ulcerative keratitis in Belgium 3,9,11–14 . Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 90%
“…A variation in bacterial isolate and antimicrobial susceptibility has been demonstrated to depend on geographical location, season, and previous antimicrobial therapy 3,9–11 . Currently, there are no publications on equine ulcerative keratitis in Belgium.…”
Section: Introductionmentioning
confidence: 99%
“…Given the little difference on the frequency and the prevalence of the isolated fungi, Aspergillus flavus, Aspergillus fumigatus, and Aspergillus niger were the most common etiological agents have been isolated from eyes of healthy and diseased equine, which is consistent with several previous studies [35,40,41,43]. Similar studies revealed that Aspergillus and Fusarium counts for one-third of all major causes of traumatic keratitis [35,40,49], while some other fungal genera could be isolated such as Candida, Penicillium, and Alternaria [11,14,23,42]. In the same line, several previous works concluded that mixed infections of Aspergillus and Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 88%
“…This may relate to the fact that a higher number of equines were examined in our study versus the majority of the previous reports worldwide [ 17 , 40 ]. Alternatively, the difference in the prevalence of fungal infection compared to our study might be attributed to the hypothesis that the seasonal variation and temperature conditions, housing and management conditions might influence the epidemiological pattern of keratomycosis [ 35 , 49 ]. Along the same line, equine fungal keratitis is usually recorded in warm and humid climate regions, which suggest that seasonal variation is an important factor influencing the occurrence of the disease [ 31 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 89%
“…Lagen Keratitiden vor, gehörten die isolierten Bakterien am häufigsten zu den grampositiven Gattungen Streptococcus und Staphylococcus (Keller und Hendrix 2005, Moore et al 1995, Mustikka et al 2020, Sauer et al 2003, sowie zu den gramnegativen Gattungen Pseudomonas (Keller und Hendrix 2005, Moore et al 1995, Moore et al 1983, Sauer et al 2003 und Acinetobacter (Moore et al 1995, Moore et al 1983 und zur Familie der Enterobacteriaceae (Moore et al 1995, Moore et al 1983.…”
Section: Gramnegative Gattungenunclassified